Effect of Varying Stocking Density on Growth and Survival of Catla catla Fry in Nursery Cisterns - A.M., Mondal; H., Shivananda Murthy; S.K., Satheesha (Fishery Technology, 2025)
Nursery rearing of carps is one of the important management practices for successful fish culture. Better health, growth and survival of the fish seed can be achieved by appropriate rearing methods. This study was undertaken to determine the optimum stocking density of Catla catla fry in nursery ponds. Catla spawn were stocked at the rate of 2.5, 3.0, 3.5 and 4.0 million, ha"1 in triplicate cisterns and designated as Sj, S2, S3, and S4, respectively. They were fed with a diet containing 38.5% protein (soya flour and fish meal based). The best growth and survival of catla fry were recorded in Sj followed by S2, S3, and S4. However, S4 (4.0 million, ha"1) was found to be cost effective with higher net return.